2017
DOI: 10.1111/idj.12360
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of oral health with general health and NCDs: a brief review

Abstract: Oral health is closely related to systemic health. Periodontitis, a chronic inflammatory disease which is highly prevalent worldwide, interacts with a variety of noncommunicable diseases (NCDs). It is a risk factor in the complex pathogenesis of diabetes mellitus and cardiovascular disease and plays a role in the development of endocarditis and recurrent pneumonia in elderly people. However, the available data may be interpreted in different ways, and more and better-designed studies are still needed to answer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
114
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(120 citation statements)
references
References 43 publications
0
114
0
6
Order By: Relevance
“…Tooth loss can substantially impair one's quality of life, causing limited chewing ability, poor dietary intake and functional disorders [1]. Research has shown diabetes and cardiovascular diseases to associate with oral health and tooth loss [2][3][4][5], and elevated glucose levels with common periodontal disease [6][7][8]. Similar finding has been reported between glucose concentration and the number of teeth [8].…”
Section: Introductionmentioning
confidence: 61%
“…Tooth loss can substantially impair one's quality of life, causing limited chewing ability, poor dietary intake and functional disorders [1]. Research has shown diabetes and cardiovascular diseases to associate with oral health and tooth loss [2][3][4][5], and elevated glucose levels with common periodontal disease [6][7][8]. Similar finding has been reported between glucose concentration and the number of teeth [8].…”
Section: Introductionmentioning
confidence: 61%
“…Das Zusammenwirken zwischen Allgemeinerkrankungen und der (dentalen als auch parodontalen) Mundgesundheit, insbesondere bezüglich der parodontalen Entzündungslast gilt heutzutage als nachgewiesen, wenngleich kausale Beziehungen schwierig zu beweisen sind [21,22]. Bidirektionale Beziehungen zwischen Mund-und Allgemeingesundheit sind dabei ebenso möglich wie eine…”
Section: Risikofaktoren I: Allgemeinerkrankungunclassified
“…2 If not treated, periodontitis is a risk factor for prominent noncommunicable diseases, including pneumonia, gastritis, diabetes mellitus, and chronic renal disorders; also, the number of lost teeth is predictive of mortality by cardiovascular conditions. 3 As a multifactorial disease, genetic and inhibiting their translation. Approximately 50% of the microRNA genes are associated with CpG islands, and their expression may be regulated by DNA methylation pathways.…”
Section: Introductionmentioning
confidence: 99%